Reframing Decadence : C. P. Cavafy's Imaginary Portraits - Jeffreys, Peter (Book collections on Project MUSE., 2015)
During his sojourn in England during the 1870s, a young Cavafy found himself enthralled by the aesthetic movement of cosmopolitan London. It was during these years that he encountered the canvases and personalities of Pre-Raphaelite painters, including Burne-Jones and Whistler, as well as works of aesthetic writers who were effecting a revolution in British literary culture and channeling influences from France that would gradually coalesce into an international decadent movement. In Reframing Decadence Peter Jeffreys returns us to this critical period of Cavafy's life, showing the poet's creative indebtedness to British and French avant-garde aesthetes whose collective impact on his poetry proved to be profound. In the process, Jeffreys offers a critical reappraisal of Cavafy's relation to Victorian aestheticism and French literary decadence. Foremost among the tropes of decadence that captivated Cavafy were the decline of imperial Rome, the rise of Christianity, and the lingering twilight of Byzantium. The influence of Walter Pater on Cavafy's view of classical and late-antique history was immense, inflected as it was with an unapologetic homoerotic aesthetic that Cavafy would adopt as his own, making Pater's imaginary portraits an important touchstone for his own historicizing poetry. Cavafy would move beyond Pater to explore a more openly homoerotic sensuality but he never quite abandoned this rich Victorian legacy, one that contributed greatly to his emergence as a global poet. Jeffreys concludes by considering Cavafy's current popularity as a gay poet and his curious relation to kitsch as manifest in his ongoing popularity via translation and visual media.